Experimental study on hydrodynamic behaviour of nanofluid particle moving through an immiscible quiescent liquid - Hasanpreet Kaur; Amit Sobti; Ravinder K. Wanchoo; Amrit P. Toor (Results in Engineering, 2022)
In the present study, experiments were conducted to study the motion of nanofluid drops moving through an immiscible quiescent liquid for the liquid-liquid extraction process. An extensive set of data in terms of terminal velocity were generated using three different systems (Chlorobenzene, Tetrachloroethylene, and Nitrobenzene) covering a wide range of properties. To elucidate the effect of the addition of nanoparticles on hydrodynamic parameters, four nanoparticles (SiO2, Al2O3, ZnO, and MWCNTs) have been taken. It is observed that with the addition of nanoparticles into the system, the terminal velocity increases up to an optimum concentration of nanoparticles, beyond which it started to decrease. On the addition of nanoparticles to the base fluid, the internal circulation within the drop increases due to Brownian motion and micro convection which in turn leads to an increase in terminal velocity and a decrease in the drag coefficient. Based on the observed data, the existing model of Grace et al. [1] for contaminated drops and bubbles, is extended to predict the terminal velocity and drag coefficient for nanofluids in terms of J and H factors. The J factor has been modified, Jmod=J(1+a(φτbdτcd)b), to account for the presence of nanoparticles in terms of nanoparticle volume fraction (ɸ), the time scale for Brownian motion diffusion (τbd), and the time scale for nano convection diffusion (τcd). The proposed correlation predicts the experimental data well to within a reasonable accuracy of ±8% with MRQE and %ARE of 0.038 and 2.99%, respectively for terminal velocity and 0.081 and 6.28%, respectively for the drag coefficient.